Revitalização urbana: uma questão de raça - Silva, Leonardo Santos Aguiar da (2019)
Our aim, with this research, is to discuss the territory questions and hausing problematic, analyzing how we have been producing ways of being onwards the urban area management. According to Michel Foucault, Frantz Fanon and Achille Mbembe’s studies, we are proposing, as a general objetive, a problematization of the speeches and urban revitalization practices, analyzing ways of objetification, subjectivation and government. Our specific objectives are: a) identify and analyze the speeches and practices that support these revitalization processes; b) discuss what notion of revitalization has been produced; c) analyze what cities and lives are produced or rejected in these revitalization projects. To address these questions, we investigated the conflict between the afro-bahian handicraft workers and the public authorities for the continuity in the Conceição Beach’s Arches Slope’s community, in the Historic Center of Salvador. The analysis materials used were public documents, as articles circulated in press, publications in social medias and official documents posted by the public authorities in internet. Based on these analysis, we concluded that this black population were turned into a target of arbitrary actions (at times, illegal) by the State, with the aim of banish them out of the territory. We also problematized the objetification strategies of these lives and the double movement of invisibilization and attribution of disqualifying signs about the ways of being observed in the Arches. Furthermore, we analyzed how the racism is used as a strategic provider that founds the construction of the concept of life sustained in these urban revitalization projects. Lastly, we understood that, despite the acknowledge of the Historic Center of Salvador as an afrocentered baianity enhancement temple, especially for the tourism industry, in this territory there is an implementation of government ways of the black lives guided by the animosity and intimidation. These political actions complement themselves, so it is necessary the execution of social exclusion politics to the establishment of new urban worlds on duty of the mercantilization perspective of these urban territories, within the framework of an urban gentrification.